ANALYSIS OF PERFORMANCE OF ROAD MT. HARYONO IN SAMARINDA - ARI, AS' (KURVA S JURNAL MAHASISWA, 2018)
Road Mt. Haryono ^ is the way Local the function serves the freight local travel characteristics at close range, average speed is low, and the number of driveways are not at the limit . Road Mt. Haryono ^ This includes class III roads category C. The development of various aspects of current life enhancing activities of society. These things have an impact on the development of transport facilities and infrastructure that facilitates the movement is happening. The road is one of the infrastructures in the army transportation function providing service on traffic flow. On the basis of this, then do research on how the performance of the vehicle through road of Mt. Haryono in Samarinda against the development of current that occurs from time to time. As for performance analysis in Road Mt. Haryono this Manual uses the capacity of the way Indonesia (MKJI ' 1997), which describe the UR-1 Form based on the form of the General conditions and Geometric way, UR-2 advanced data input form i.e. the flow and composition of traffic and Obstacles aside, the UR-3 form Analysis of free flow speed of light vehicles, the capacity and speed of light vehicles. In research performance analysis Standards Mt. Haryono the survey was carried out during peak hours 3 Sunday, the first Sunday at simpang White Water, second week at Simpang Bangris and week three at simpang m. Said. the survey was conducted at 06.00 A.m. until 22.00 night . After the calculation is performed against the data, at the junction with white water segment 1 peak hours occurs on the day of Thursday, in may the Volume of traffic 1950.0 junior/hour, the degree of Saturation of 0,59, speed, 38 km/h, journey time 0.0657 hours and service levels are at the level of the mean C. the current stable zone, the driver in selecting speed limit. at the simpang Bangris segment 2 hour Summit took place on Saturday, in the Volume of traffic may 1678.70 junior/hour, the degree of Saturation of 0, 52, 3 Speed6 km/h, journey time 0.0694 hours and service levels are at level C. that means the current stable Zone, the driver in selecting the speed limit. Then at simpang m. Said segment 3 hour peak occurred on the day of Friday, on Volume of traffic can be 1621.30 junior high school/hour, the degree of Saturation of 0,51, 3 Speed6 km/h, journey time 0.0694 hours and service levels are at level C that means current Zone. stable, the driver in selecting the speed limit.